Edupreneurial Innovations in Mathematical Literacy and Global Instructional Practices - Sumliyah, Sumliyah; Wardono, Wardono; Mariani, Scolastika; Waluya, Stevanus Budi; Pujiastuti, Emi; Ani, Nyree (Pandawan, 2026)
This study provides a global synthesis of pedagogical innovations and research developments in mathematical literacy from 2022 to 2026, uniquely emphasizing an edupreneurial perspective that integrates entrepreneurial creativity into mathematics education through innovative teaching and learning practices. The analysis utilizes the Scopus, ERIC, and Google Scholar databases to identify global trends and research gaps. Employing the Systematic Literature Review (SLR) method based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework, a total of 564 articles were initially identified, with selected studies analyzed to address predefined research questions. The review highlights that research on mathematical literacy is predominantly characterized by qualitative and quantitative approaches, with junior high school students as the most frequent subjects and research settings. A growing trend in edupreneurial pedagogical practices is evident through the integration of contextual problem-solving strategies, ethnomathematical perspectives, and technology-enhanced learning models. Recommendations for future research and policy include strengthening teacher conceptual understanding of mathematical literacy, developing contextually rich assessment models, advancing technology-integrated instruction, and expanding research toward psychological factors influencing mathematical literacy. Moreover, the study underscores the need for increased research at the vocational education level and calls for education policymakers to design and implement professional development programs aimed at enhancing teachers’ and students’ competencies in mathematical literacy through innovative, entrepreneurial-based learning approaches.